Backward semi-linear parabolic equations with time-dependent coefficients and local Lipschitz source. (13th April 2018) - Nho Hào, Dinh; Van Duc, Nguyen; Van Thang, Nguyen
Abstract: Let H be a Hilbert space with the inner product and the norm, a positive self-adjoint unbounded time-dependent operator on H and . We establish stability estimates of Hölder type and propose a regularization method with error estimates of Hölder type for the ill-posed backward semi-linear parabolic equation with the source function f satisfying a local Lipschitz condition.